Penerapan Algoritma Ant Colony Optimization Pada Aplikasi Pemandu Wisata Provinsi Sumatera Utara Berbasis Android - Zakarial Anshory (Journal of Computer System and Informatics (JoSYC), 2020)
North Sumatra Province is a province that is rich in tourism. Lots of interesting tourism spots are scattered throughout the Province. But tourists tend to only know famous tourist areas in North Sumatra Province, such as Lake Toba and Samosir Island. In everyday life people are more familiar with the term guide than a tour guide or tour guide. A tour guide is basically someone who accompanies, provides information and guidance as well as advice to tourists in conducting their tour activities. The problem that often arises when tour guides carry out tourism activities, the tour guides must be on time to arrive at the destination, as well as share the schedule for tourists to do tourism activities, whereas not all tourists are on time before carrying out their tourism activities, and most tour guides only know the usual places and routes but not the closest route from the starting point, This can slow down tourism activities. The method to be used in determining these tourist attractions is the Ant Colony Optimization Algorithm, Ant Colony Optimization (ACO) adopted from the behavior of ant colonies that known as the ant system